Mistakes and Difficulties Analysis of Junior High School Students on The Pythagorean Theorem Material and its Alternative Solutions - sumarsih - sumarsih (Universitas Sebelas Maret, 2020)
This study aims to analyze the mistakes and difficulties of students in the Pythagorean theorem and its alternative solutions. The sample was selected by purposive sampling. Evaluative analysis was carried out on the results of tests, documents, and interviews with eighth grade students at SMP Negeri 1 Masaran. Students' mistakes were discovered: incorrectly changing the Pythagorean formula from a square to a root form, determining the side length of a special right triangle, and making a sketch of the problem form a story. The causes of student mistakes include: objects in the form of facts of quadratic symbols and square roots are ignored, difficulty understanding concrete facts in special right triangles, weak to transfer ideas from problems presented with pictures, unable to describe contextually a right triangle sketch of the problem form of the story, and students tend to use routine procedures rather than non-routine procedures. The alternative solution is to strengthen numeracy literacy and increase the practice of using non-routine procedures in solving problems.